Strategies for sustainable agricultural development in the Ethiopian highlands - Pender, J.L.; Gebremedhin, Berhanu; Benin, Samuel; Ehui, Simeon K. (Wiley, 2001)
Land degradation is a severe problem in the Ethiopian highlands. Factors that may be important in influencing land management and its impacts on resources and human welfare include low and uncertain rainfall in much of the highlands, limited market access and market development, land tenure insecurity, credit constraints, farmers' limited education or limited awareness of technological opportunities, poverty, and government policies and programs affecting these factors. Evidence on the impacts of such factors and possible strategies for overcoming land degradation and poverty in the Ethiopian highlands is still sparse. There are recent studies that did not consider most of the socioeconomic and policy factors mentioned above. This study addresses these issues using data on changes in land management and resource and poverty indicators collected in a large number of villages in the Ethiopian highlands. It investigates the impacts of policy factors such as land tenure policies, the presence of various programs and investments in infrastructure, as well as impacts of population pressure and control of omitted variable bias caused by unobservable fixed factors.